2023
DOI: 10.1186/s13756-023-01290-4
|View full text |Cite
|
Sign up to set email alerts
|

How biofilm changes our understanding of cleaning and disinfection

Jean-Yves Maillard,
Isabella Centeleghe

Abstract: Biofilms are ubiquitous in healthcare settings. By nature, biofilms are less susceptible to antimicrobials and are associated with healthcare-associated infections (HAI). Resistance of biofilm to antimicrobials is multifactorial with the presence of a matrix composed of extracellular polymeric substances and eDNA, being a major contributing factor. The usual multispecies composition of environmental biofilms can also impact on antimicrobial efficacy. In healthcare settings, two main types of biofilms are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 132 publications
(197 reference statements)
0
7
0
Order By: Relevance
“…Multiple species of microorganisms formed biofilms in 93% of samples. Polymicrobial biofilms are less susceptible to disinfection than mono-bacterial biofilms [91,93]. Centeleghe and colleagues published (2023) the first study that confirmed that Klebsiella pneumoniae can survive for a long time on dry surfaces as a dry surface biofilm (DSB).…”
Section: Studies On Mdr Klebsiella Pneumoniae Biofilmmentioning
confidence: 99%
“…Multiple species of microorganisms formed biofilms in 93% of samples. Polymicrobial biofilms are less susceptible to disinfection than mono-bacterial biofilms [91,93]. Centeleghe and colleagues published (2023) the first study that confirmed that Klebsiella pneumoniae can survive for a long time on dry surfaces as a dry surface biofilm (DSB).…”
Section: Studies On Mdr Klebsiella Pneumoniae Biofilmmentioning
confidence: 99%
“…Medical biofilms can contain a single microbe or be composed of several different microbes embedded in extracellular polymeric substances (EPSs). The EPS is typically composed of "polysaccharides, proteins, lipids, enzymes, extracellular-DNA (eDNA), and water" [22] (p. 1). Only actively growing or vegetative Bacillus cells produce EPSs.…”
Section: Medical Biofilmsmentioning
confidence: 99%
“…While it is well established that disinfectants can effectively kill or inactivate pathogenic microorganisms on surfaces, microorganisms can be less susceptible to disinfectants when in an environmental biofilm ( Maillard and Centeleghe, 2023 ). This “resistance” to disinfection may increase as biofilms age and secrete thicker and more compact layers of extracellular polymeric substances.…”
Section: Disinfectant Efficacy Against Biofilms Versus Planktonic Cellsmentioning
confidence: 99%